Pengaruh Saham Syariah, Sukuk dan Reksadana Syariah Terhadap Pertumbuhan Ekonomi Indonesia (Tahun 2012 - Tahun 2017) - I Irawan; Zulia Almaida Siregar (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2019)
This study has a long-term goal, namely to see how much influence Islamic stocks have on economic growth, the influence of sukuk on economic growth, the effect of Islamic mutual funds on economic growth, and the influence of Islamic stocks, sukuk, and Islamic mutual funds on economic growth (2012 period up to in 2017). The method that will be used in this research is the research approach, data collection obtained from the official website of the Financial Services Authority (FSA) and the Central Statistics Agency (CSA), literature studies related to research topics, analysis multiple linear regression, classic assumption test, statistical test, and focus group discussion (FGD). The variable Sharia Stock Index (ISSI) has a p-value of 0,105 > 0,05 which means it is not significant, while tcount 1,696 < ttable 2,080 means that it is not significant. Then the Islamic Stock Index (ISI) partially does not affect Gross Domestic Product (GDP), or H1 is rejected. Sukuk variable has a p-value of 0,441 > 0,05 which means it is not significant, while tcount 0,785 < ttable 2,10 means not significant. Then sukuk partially does not affect Gross Domestic Product (GDP), or H2 is rejected. Islamic mutual fund variables have a p-value of 0,761 > 0,05 which means it is not significant, while the ttest is -0.358 < ttable 2,080 means that it is not significant. Then sharia mutual funds do not partially affect the Gross Domestic Product (GDP), or H3 is rejected. Simultaneously, the Islamic Stock Index (ISI), sukuk, and Islamic mutual funds variables have a positive influence on Gross Domestic Product (GDP) based on the Ftest where Fcount > Ftable (7,368 > 2,080) while the level is significant at 0,002 < 0,05. This means that the hypothesis H4 is accepted, meaning that the better the Islamic Stock Index (ISI), sukuk, and Islamic mutual funds, the more the number of Gross Domestic Product (GDP) increases.